Relaciones Empíricas Entre Empresas y Bancos. Una Visión Financiera (2019)
The research group on economics and business carried out the project "theoretical and empiricalaspects of firms – banks" relationship. The general objective was developing an investigationabout the channels and variables through which a relationship is establish between firms returnand performance, on one hand, and banks´ solvency and returns´ on the other.The main purpose of this paper is discussing the importance of firms´ financial management onfinancial sector credit policy establishment.